Analysis of Student Learning Independence in State Junior High School 14 Semarang - Arie Wahyuni; Destia Wahyu Hidayati (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
Student independence in learning must be grown, so that they can develop their creative ideas without the full support of the teacher. Learning independence is largely determined by applicable learning media and models. Therefore, it is necessary to analyze the independence of learning. Students as a basis for consideration of the use of a particular learning model or environment. The implementation of this research was at SMP Negeri 14 Semarang. The data analysis technique used is simple descriptive statistics and qualitative analysis. Mass Research Recommendations to be able to do this in the future, a learning model is needed that incorporates elements of technology to increase student learning independence through student activation learning models in schools.